Acute Aortic Dissection and Medullary Ischemia in a Patient with Marfan syndrome - Góes, Gustavo Henrique Belarmino; Albuquerque, Eugenio Soares de; Sepulveda, Diana Patricia Lamprea; Castillo, José Maria Del; Sousa Filho, José Breno de; Lima, Ricardo de Carvalho; Filho, Dário Celestino Sobral (International Journal of Innovative Research in Medical Science, 2019)
Marfan syndrome (MS) is an autosomal dominant inherited connective tissue disease. The systemic complications of this disorder occur due to osteo-articular, cardiovascular, and ophthalmologic alterations. The cardiovascular involvement of MS is characterized mainly by aortic root and arch changes, resulting in increased susceptibility for the development of aneurysms. In the present study, we describe a case of type B abdominal aortic dissection in a patient with MS followed by spinal cord ischemia that rapidly evolved to paraplegia. Although rare, medullary ischemia is associated with a poor prognosis, as noted in the present case, wherein the patient died.